An Integrated Mycobacterium tuberculosis Infection Session: Utilizing an Online Collaborative Platform in a Synchronous Classroom Setting - Trent D. Jackman; Anne M. Dersch; Tracey A. H. Taylor; Claudio Cortes (Association of American Medical Colleges, 2021)
Introduction Tuberculosis (TB) remains a major public health concern worldwide. It is important to provide high-quality instructional sessions to students about the pathogenesis and risk factors of TB, as medical students are likely to encounter TB infections in clinical practice. Methods We describe an interactive instructional session integrating immunology and microbiology concepts of Mycobacterium tuberculosis infection that was presented to first-year medical students in their respiratory organ systems course. The session included a pretest primer followed by a brief review of mucosal immunity with an emphasis on the respiratory system. Using an online collaborative application, learners created a study guide on a shared spreadsheet while faculty provided real-time feedback. Following the cloud-based portion, faculty presented interactive lectures using student-created content. The session concluded with a formative posttest. We evaluated the session with responses to an optional student survey. Results One hundred fourteen students (37% male and 63% female) completed the survey across 4 years from 2016 to 2019. The session received high student satisfaction ratings across five questions, with 83% of students indicating they were slightly satisfied to strongly satisfied. The students had an absolute increase in their scores of 31% on the posttest as compared to the pretest mean (p < .001). Discussion We developed an interactive TB instructional session that integrates disciplines, contains real-time instructor feedback, and promotes teamwork in a large class setting. The session allows medical students to learn content and create their own study guide using online collaboration technology.